SOME CHARACTERISTICS OF THE ART OF USING SINO-VIETNAMESE WORDS IN QUOC AM THI TAP (NGUYEN TRAI) - Vu Thi Ngoc Kim (Tạp chí Khoa học, 2024)
Quoc Am Thi Tap is a classic piece of Vietnamese literature, particularly in the poetry genre. The work exhibits cross-cultural interchange between Vietnamese and Chinese civilizations and has a solid cultural and historical influence. In addition to enhancing the language, the work's usage of Sino-Vietnamese terms produces rich and varied artistic values. The author highlights some features of the Quoc Am Thi Tap's artistic uses of Sino-Vietnamese vocabulary to highlight significant turning points in the evolution of the language and writing system.